2008
DOI: 10.1007/s11255-008-9508-7
|View full text |Cite
|
Sign up to set email alerts
|

Creatinine reabsorption by the aged kidney

Abstract: Our findings indicate that there seems to be a net reabsorption of creatinine in the renal tubules of healthy old persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 14 publications
(13 reference statements)
1
45
0
2
Order By: Relevance
“…ROS causes the elevation of the free radical level within the body. Free radicals could damage the structure and function of various tissues, including renal tissue [4]. Histopathological damage on the structure and function of renal tissue has been previously reported as glomeruli hypertrophy, glomeruschlerosis, and swelling, apoptosis, and the necrosis of renal proximal tubular epithelial cells [5].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS causes the elevation of the free radical level within the body. Free radicals could damage the structure and function of various tissues, including renal tissue [4]. Histopathological damage on the structure and function of renal tissue has been previously reported as glomeruli hypertrophy, glomeruschlerosis, and swelling, apoptosis, and the necrosis of renal proximal tubular epithelial cells [5].…”
Section: Resultsmentioning
confidence: 99%
“…ROS within the body will elevate free radicals. Free radicals are able to damage various tissues in the body, including renal proximal tubular tissue [4].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of intestinal dialysis have shown a daily flow of 71 grams of urea, 2.9 grams of creatinine, 2.5 grams of uric acid and 2.0 grams of phosphate into the intestinal fluid (16). Accordingly, various invasive and noninvasive attempts including external gut fistula, intestinal dialysis, induced diarrhea, and administration of oral sorbents and/or encapsulated urease enzyme have been made to extract uremic waste from the gastrointestinal tract (2,3,(7)(8)(9)(10)(11)(12)(13)(14)(15). The second part of our protocol was the use of prebiotic.…”
Section: Discussionmentioning
confidence: 99%
“…At present, AST-120 is widely used as an approved drug in Japan for the treatment of approximately 20,000 undialysed uremic patients to delay the progression of CRF. However, AST-120 is not yet available outside Japan (11)(12). The aim of our proposed dialysis free protocol is to introduce another type of renal replacement therapy for selective patients with advanced CKD.…”
mentioning
confidence: 99%
“…More recently other solutes, including urea, uric acid, and lithium, have been investigated with the goal of improvement in the diagnostic ability to distinguish between PRA and ATN. [44][45][46][47][48][49][50][51][52][53][54] In an effort to evaluate these studies and the particular problems with each solute, we will briefly review the physiology of their renal handling in water deprivation states.…”
Section: Introductionmentioning
confidence: 99%